Serum p53 Antibody Is Not Associated with p53 Immunoreactivity in Patients with Pancreatobiliary Cancers. (18th December 2013) - Umeda, Junko; Itoi, Takao; Sofuni, Atsushi; Itokawa, Fumihide; Kurihara, Toshio; Tsuchiya, Takayoshi; Ishii, Kentaro; Tsuji, Shujiro; Ikeuchi, Nobuhito; Tanaka, Reina; Tonozuka, Ryosuke; Honjo, Mitsuyoshi; et al.
Abstract : Background . Recent diagnostic imaging tests contribute to improving the diagnosis of pancreatobiliary cancers. However, it is not practical to perform these tests for all patients as screening. Thus, less-invasive and simple screening tests are still required. A method to detect the IgG antibody induced in serum against the p53 protein accumulating due to p53 gene mutation, as a biomarker, was developed around 1990. Method . 35 patients with pancreatic cancer, 12 patients with biliary tract cancer, and 31 patients with benign pancreatobiliary diseases were entered into this study. Measurement of serum anti-p53 antibody was conducted in all patients. In addition, the rate of p53 protein overexpression was examined in those cases that could be examined pathologically. Result . Among all patients in the pancreatic cancer and biliary tract cancer groups, there was no patient with serum anti-p53 antibody positive value that exceeded the standard value. The rate of p53 protein overexpression was 48.0% in the patients with pancreatobiliary cancers and 0% in the benign pancreatobiliary diseases group. Conclusion . Serum anti-p53 antibody measurement does not contribute to the diagnosis of pancreatobiliary cancers. Instead, traditional p53 immunostaining still appears to be valuable in combination with standard procedures.